Remote control of a moving vehicle - Suzaley, Sulaiman (2008)
The remote control of a moving vehicle is a project that uses a radio frequency to control the maneuver and movement of the model car. The Peripheral Integration Controller (PIC) 16F877A is used in this project. The LCD is placed at the remote control to help user to determine the maneuver angle of the model car. The potentiometer is used as a joystick for the transmitter. There are 2 potentiometer used in this project. The first potentiometer is used to control the maneuver angle and the other one is used to control the movement of the car. The stepper motor is used instead of DC motor to maneuver the car. This is because the stepper motor is more precise than DC motor. DC motor is used to for the movement of the car. The stepper motor and DC motor are interface with PIC on receiver board. The frequency of RF module that used is 343MHz. The car will maneuver to the left or right with the exact angle and the angle is already program in PIC. The angle that has been program in the PIC is 5°, 15° and 45°. To ensure the maneuver more precise, the movement of the motor will stop whenever the car is maneuvering to the left or right. The head light will automatically ON when the car detect the surrounding a little bit darker than usual. The bottom light of the car will automatically ON whenever the surrounding is completely dark. There are also 2 other head light that can be ON using the remote control.